Rapid Appraisals of the Transformation Strategy Required to Sustain Dengue Vector Control During and After the COVID-19 Pandemic in Indonesia - Sulistyawati S; Yuliansyah H; Sukesi TW; Khusna AN; Mulasari SA; Tentama F; Sudarsono B; Ghozali FA (Dove Medical Press, 2023)
Sulistyawati Sulistyawati,1 Herman Yuliansyah,2 Tri Wahyuni Sukesi,1 Arfiani Nur Khusna,2 Surahma Asti Mulasari,1 Fatwa Tentama,3 Bambang Sudarsono,4 Fanani Arief Ghozali5 1Faculty of Public Health, Universitas Ahmad Dahlan, Yogyakarta, Indonesia; 2Department of Informatics, Faculty of Industrial Technology, Universitas Ahmad Dahlan, Yogyakarta, Indonesia; 3Faculty of Psychology, Universitas Ahmad Dahlan, Yogyakarta, Indonesia; 4Department of Automotive Technology Vocational Education, Faculty of Teacher Training and Education, Universitas Ahmad Dahlan, Yogyakarta, Indonesia; 5Department of Electronics Engineering Vocational Education, Faculty of Teacher Training and Education, Universitas Ahmad Dahlan, Yogyakarta, IndonesiaCorrespondence: Sulistyawati Sulistyawati, Faculty of Public Health, Universitas Ahmad Dahlan, Kampus 3, Jln Prof. Dr. Soepomo, Janturan, Umbulharjo, Yogyakarta, Indonesia, Email sulistyawati.suyanto@ikm.uad.ac.idPurpose: This research aimed to observe the gap for improvement in dengue vector control during COVID-19, considering two stakeholders: the government and society. We formulated two research questions: 1) How is the government managing dengue vector control during the COVID-19 pandemic? 2) What is the situation of dengue disease, its vectors, and vector control in the community?Methods: This study uses multiple approaches: policy review, social listening using Twitter analysis, and interviews. A policy review was employed to capture the journey of dengue vector control in Indonesia from dengue found in Indonesia until the COVID-19 pandemic. Twitter data captured public opinions through social media about dengue and vector control. Interviews involved program implementers that consider knowing the situation in the field of dengue and its vector control. The informant was selected through purposive sampling.Results: To control dengue disease, the Indonesian government has released regulations about dengue vector control that adjusts the COVID-19 situation, but vector control is still not running optimally, resulting in the data supply for policy not running well.Conclusion: Dengue cases continued during the COVID-19 pandemic, even in some places stated an outbreak occurred. Vector control does not work correctly during the COVID-19 pandemic due to social restrictions. It is recommended to encourage the implementation of community empowerment through one house, one jumantik, which is equipped with self-reporting to mitigate and respond to similar situations as the pandemic.Keywords: dengue, COVID-19, vector control, policy, pandemic